THE NUTRITIONAL VALUE OF CAULIFLOWER AND ITS MAIN BENEFITS (Journal of Universal Science Research, 2024)
The cauliflower is  an annual plant, vegetable crop belonging to the cauliflower-cabbage family. After producing 15-20 leaves, it forms a head (300-500 g) in the upper part of the stem. The head consists of many short florets, and its shape (large and small, degree of growth) depends on the type of cauliflower and growing conditions. After the head of cabbage is formed, some of the stems continue to grow, turning into inflorescences, flowers and seeds. The flower is white or yellow. Cauliflower is biologically similar to ordinary cabbage, but it cooks faster